Heterotopic Gastric Mucosa in the Distal Part of Esophagus in a Teenager: Case Report. Issue 42 (October 2015) - Lupu, Vasile Valeriu; Ignat, Ancuta; Paduraru, Gabriela; Mihaila, Doina; Burlea, Marin; Ciubara, Anamaria
Abstract : Abstract: Heterotopic gastric mucosa (HGM) of the esophagus is a congenital anomaly consisting of ectopic gastric mucosa. It may be connected with disorders of the upper gastrointestinal tract, exacerbated by Helicobacter pylori. The diagnosis of HGM is confirmed via endoscopy with biopsy. Histopathology provides the definitive diagnosis by demonstrating gastric mucosa adjacent to normal esophageal mucosa. HGM located in the distal esophagus needs differentiation from Barrett's esophagus. Barrett's esophagus is a well-known premalignant injury for adenocarcinoma of the esophagus. Malignant progression of HGM occurs in a stepwise pattern, following the metaplasia–dysplasia–adenocarcinoma sequence. We present a rare case of a teenage girl with HGM located in the distal esophagus, associated with chronic gastritis and biliary duodenogastric reflux. Endoscopy combined with biopsies is a mandatory method in clinical evaluation of metaplastic and nonmetaplastic changes within HGM of the esophagus.